Revisiting the Concepts of Rights, Obligations and Injury in the Invocation of State Responsibility in Inter-State Adjudication - Fernandez, Gemmo Bautista (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
This article delves into the two-tiered approach to standing presented by Article 42 and 48 of the International Law Commission's Draft Articles on State Responsibility. Particularly it highlights the issues brought about by the articles, ranging from overbreadth, potential for abuse, desirability of distinction, and legal status. It also looks into the decisions of the International Court of Justice and observes that, while there may be practice from states in raising such a claim to standing, there is an absence of judicial recognition with regard to Article 48, thereby highlighting its status as lex ferenda. After highlighting the issues and the status of the two-tiered approach, the Article revisits the concepts of rights, obligations, and injury, and demonstrates the merits of the reunification of the two articles. First, the article deals with the issue of the distinction between "rights" under Article 42 and "legal interests" used in Article 48. The article seeks to eliminate this distinction by relying on "rights" alone as a basis for the invocation of state responsibility in inter-state adjudication. Second, it submits the international obligations, even orga omnes partes and erga omnes, could be "bilateralised" thereby eliminating the need for different approaches based on the nature of the obligations. Third, the article addresses the issue of "injury" and notes that both classes of states viewed by the two articles are in fact injured if their "rights" have been violated through a breach of obligation by a responsible state. Lastly, it delves into the effect of the reunification of the articles on the implementation of state responsibility. It also endeavours to clarify issues surrounding the implementation of obligations erga omnes such as whether community decisions are required for its invocation and whether the directly affected states have the primacy of action over those states which are not.
Keywords: International law; International law (Human rights)